On the provisions regarding access to and benefit-sharing of MGRs under the BBNJ agreement: from the perspective of the concept of a maritime community with a shared future - Wang, Chuanliang; Zhao, Mengjie; Wang, Dexin; An, Xiuwei (Frontiers in Marine Science, 2025)
The BBNJ Agreement represents a new development in the field of the law of the sea. In particular, the implementation of the provisions regarding access and benefit-sharing (hereinafter, ABS) of marine genetic resources (hereinafter, MGRs) under the BBNJ Agreement emerges as a pressing issue for contracting Parties. In the process of implementing the provisions, there arises a compelling need to reach a consensus and coordinate interests with the concept of a maritime community with a shared future (hereinafter, MCSF). The connotations of the concept of MCSF could be interpreted from three dimensions: community of maritime interests, community of maritime responsibilities and community of maritime developments. Furthermore, it also explores the practical significance of the concept of MCSF in the implementation of the provisions regarding ABS of MGRs, focusing on ownership disputes, access management, and benefit-sharing regime. As a responsible major power, China should take the concept of MCSF as a guide, providing Chinese solutions for the implementation of the provisions regarding the ABS of MGRs from both a macro-level of global marine governance and a micro-level of implementation.